Enchancing Travel Agent Employee Retention Through Career Development : The Mediating Role Of Organizational Commitment - Lina Saptaria; Aurelia Nazla Kamila Putri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the extent to which career development influences employee retention, considering organizational commitment as a mediating variable that plays a role in bridging this relationship, specifically in the context of travel agencies in the Kediri region of East Java. This study adopted a quantitative framework with a descriptive design, where a series of data were collected through questionnaires distributed to 110 individuals working as staff at corporate entities operating in the travel services sector. The Structural Equation Modeling method was applied using SmartPLS version 4.0 software. The data processing results indicate that career development has a significant and positive influence on employee retention rates. Furthermore, career development also has a positive and meaningful impact on increasing organizational commitment. This commitment to the organization, in turn, contributes significantly to the sustainability of employee retention. Further findings indicate that organizational commitment plays a significant mediating variable in facilitating the causal relationship between career development and employee retention. The practical implications of this study indicate that investing in career development can strengthen workforce stability, reduce recruitment costs, and support sustainable tourism industry growth. The uniqueness of this study lies in its focus on the under-researched travel agency sector and its integration of the role of organizational commitment as a mediator in the analyzed relationships. Career development makes employees feel valued and increases their commitment. This makes employees less likely to leave the company, thus increasing retention rates.